Determinant Factors of Santri's Entrepreneurial Motivation - Umi Khabibah; Agus Wahyudin; Amir Mahmud (Universitas Negeri Semarang, 2026)
The creation of young entrepreneur in Indonesia has been developed by the government as part of the increase and improvement of the national economy. Pesantren (Islamic boarding school) is an educational institution that potentially produces young entrepreneurs. This research aims to determine the factors that influence santri’s (Pesantren’s students) entrepreneurial motivation, such as family environment, Pesantren environment, peer environment, self-efficacy and entrepreneurial knowledge. This research is a quantitative research which applies questionnaire techniques to collect data taken from 52 santri who are active in Pesantren Fadhlul Fadhlan business unit. The results of this research show that the family environment and Pesantren environment have a positive and significant effect on santri’s entrepreneurial motivation. The peer environment has no effect on santri’s entrepreneurial motivation. Entrepreneurial knowledge moderates the influence of the peer environment on santri’s entrepreneurial motivation. Meanwhile, self-efficacy does not moderate the influence of the family environment, Pesantren environment, and peer environment on santri’s entrepreneurial motivation.